To find the function \( g(x) \) based on the reflection of the function \( f(x) = -2x + 1 \) across the x-axis, we need to understand what reflecting a function across the x-axis does to its equation.
When a function \( f(x) \) is reflected across the x-axis, the new function \( g(x) \) is given by:
\[ g(x) = -f(x) \]
Applying this to the function you provided:
- Start with \( f(x) = -2x + 1 \).
- Reflect across the x-axis:
\[ g(x) = -(-2x + 1) = 2x - 1 \]
Thus, the correct answer is:
\[ g(x) = 2x - 1 \]
So, the response is:
g(x) = \( 2x - 1 \).